A Novel Homozygous VPS13B Splice-Site Mutation Causing the Skipping of Exon 38 in a Chinese Family With Cohen Syndrome - Li, Liangshan; Bu, Xiangmao; Ji, Yuhua; Tan, Ping; Liu, Shiguo (Frontiers in Pediatrics, 2021)
Background: Cohen syndrome (CS) is a clinically heterogeneous disorder characterized by extensive phenotypic variation with autosomal recessive inheritance. VPS13B was identified to be the disease-causing gene for CS. The objectives of the present study were to screen likely pathogenic mutations of the patient with developmental delay and mental retardation, and to determinate the effect of this splice-site mutation by reverse transcription analysis. Methods: Whole exome sequencing (WES) in combination with Sanger sequencing were performed to identify the causative mutations of this CS family. Subsequently, the impact of the intronic variant on splicing was analyzed by reverse transcription and the construction of expression vector. Results: A novel homozygous splice-site mutation (c.6940+1G>T) in the VPS13B gene was identified in this proband. Sanger sequencing analysis of the cDNA demonstrated that the c.6940+1G>T variant could cause the skipping of entire exon 38, resulting in the loss of 208 nucleotides and further give rise to the generation of a premature in-frame stop codon at code 2247. Conclusions: The homozygous VPS13B splicing variant c.6940+1G>T was co-segregated with the CS phenotypes in this family and was identified to be the cause of CS after comprehensive consideration of the clinical manifestations, genetic analysis and cDNA sequencing result.